Contemporary genetics-based diagnostics of male infertility. (3rd July 2019) - Ferlin, Alberto; Dipresa, Savina; Delbarba, Andrea; Maffezzoni, Filippo; Porcelli, Teresa; Cappelli, Carlo; Foresta, Carlo
ABSTRACT: Introduction Thousands of genes are implicated in spermatogenesis, testicular development and endocrine regulation of testicular function. The genetic contribution to male infertility is therefore considerable, and basic and clinical research in the last years found a number of genes that could potentially be used in clinical practice. Research has also been pushed by new technologies for genetic analysis. However, genetic analyses currently recommended in standard clinical practice are still relatively few. Areas covered We review the genetic causes of male infertility, distinguishing those already approved for routine clinical application from those that are still not supported by adequate clinical studies or those responsible for very rare cause of male infertility. Genetic causes of male infertility vary from chromosomal abnormalities to copy number variations (CNVs), to single-gene mutations. Expert opinion Clinically, the most important aspect is related to the correct identification of subjects to be tested and the right application of genetic tests based on clear clinical data. A correct application of available genetic tests in the different forms of male infertility allows receiving a better and defined diagnosis, has an important role in clinical decision (treatment, prognosis), and allows appropriate genetic counseling especially in cases that should undergo assisted reproduction techniques.